2020
DOI: 10.3329/bjsir.v55i4.50966
|View full text |Cite
|
Sign up to set email alerts
|

Okra (Abelmoschus esculentus L.) yield influenced by Albizia leaf mould and banana peel with half dosage of NP chemical fertilizers

Abstract: Dried Albizia leaf mould (10 mt/ha) and banana peel (0.1-0.5 mt/ha) with reduced level of NP chemical fertilizers were applied on the production of okra (Abelmoschus esculentus L.).The experiment was carried out in a randomized complete block design with seven treatments. The result revealed that the combined application of 10 mt/ha leaf mould and 0.1 mt/ha banana peel with 50% NP chemical fertilizer as basal and 50% N as top dressing (T6) exhibited higher yield than recommended 100% NPK chemical fertilizer al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This is in line with Gachengo (1999), who reported that incorporating fresh Tithonia biomass at the equivalent of 5 t dry matter per hectare increased the maize yield. Gayathri and Seran (2020) stated that the combined use of leaf mould and banana peel with a reduced level of chemical fertilizers remarkably increased the fruit yield of okra than the control treatment (chemical fertilizer alone) in sandy regosal. Hafifah et al (2016) reported that the addition of the Tithonia green manure to the soil raises the total N, available P and the organic C, which may increase the pod number per plant.…”
Section: Marketable Pod Yieldmentioning
confidence: 99%
“…This is in line with Gachengo (1999), who reported that incorporating fresh Tithonia biomass at the equivalent of 5 t dry matter per hectare increased the maize yield. Gayathri and Seran (2020) stated that the combined use of leaf mould and banana peel with a reduced level of chemical fertilizers remarkably increased the fruit yield of okra than the control treatment (chemical fertilizer alone) in sandy regosal. Hafifah et al (2016) reported that the addition of the Tithonia green manure to the soil raises the total N, available P and the organic C, which may increase the pod number per plant.…”
Section: Marketable Pod Yieldmentioning
confidence: 99%